Reasons for and obstacles to cycling in opinions of residents of Debrecen, Hungary - Kosztin , Nikolett; Tőzsér , József; Csernoch , László; Balatoni , Ildikó (Applied Studies in Agribusiness and Commerce, 2017)
It is a basic aim of the European Union that due to the developments in 2014-2020 the bicycle would become one of the most often used transportation, touristic, and sports equipment. We were interested to see to what extent is bicycling present in the transportation system of Debrecen and what are the most important reasons for its residents to use the bicycles. The dedication of Debrecen to promote cycling is clearly proven by the number of newly built or resurfaced bike paths and by the fact that the University of Debrecen has introduced – alone in the region – UniBike which is a bicycle renting system brought forth by the need of its students. Here we present the developments that took place in the North Plain Region in the past few years. We have also analyzed the national and European strategies and reports on bicycling. A survey was conducted among the youth of Debrecen to explore their cycling habits. The data were evaluated using the EvaSys program. Until the end of 2011 with the help of different funds 862 km of bike paths had been built in Hungary. In the North Plain Region due to funds totaling 777 million HUF 15.7 km long bike paths had been constructed until 2015. The development of tourism in this direction is promoted by the web-pages and brochures offering bicycle-tours around Debrecen. Nevertheless, bicycling in the neighboring townships is present not as an instrument for sports and/or tourism, rather as a mean of transportation. It is a clear goal in Europe and thus in Hungary to have bike paths that can provide the means of safe cycling. In parallel, it is also important to promote the benefits of bicycling, including positive physiological effects, cost-effectiveness, and environment-friendliness to increase the proportion of those who select bicycling as an alternative.JEL Code: I15